Basic construction materials - Marotta, Theodore W. (Pearson, 2005)
For an undergraduate Construction materials course with a lab component taught in departments of Construction Management/Technology and Architecture. Offering an in-depth introduction to the real-world application of some of the most fundamental materials used in construction today, this informative and practical text reflects the latest industry standards from ASTM and ACI, and fully prepares students for entry into the construction industry or for further study in construction methods, specification writing, design methods, or related engineering programs.